Bovine meat and milk production in the Osa Peninsula, Costa Rica (UNED Research Journal, 2023)
Introduction: The cattle industry in Osa Peninsula dates back to 1948, and is a significant part of local development. By understanding its current state, improvement opportunities can be identified for cattle breeding farms. Objective: To characterize bovine production in Bahia Drake and Puerto Jimenez, Puntarenas, Costa Rica. Methodology: We visited production systems from August 2017 to April 2018, and made interviews on producers, land, herd and other aspects. Results: We evaluated 43 production systems in P. Jimenez and 27 in Drake. In P.  Jimenez, 81% of the people in charge of the farm were men and 95% landowners (mean: 35 years of experience). Mean farm size was 88ha, with 63% of the area dedicated to pasture. Mean herd size was 77 animals, with an animal load of 1,61AU/ha. Corresponding values for Bahía Drake were 89% men, 95% landowners, 25 year experience; 79ha, with 39% pasture; 44 animals, and 1,21UA/ha. Conclusion: At both sites, most of the people in charge are male owners, and there are no marked differences in farms or herds between sites.
Keywords: livestock; herd structure; forages; feed inputs; land use; productive and reproductive indicators